A review of the pharmacokinetics, efficacy and safety of high‐purity factor X for the prophylactic treatment of hereditary factor X deficiency. Issue 4 (2nd May 2022) - Payne, Jeanette; Batsuli, Glaivy; Leavitt, Andrew D.; Mathias, Mary; McGuinn, Catherine E.
Abstract: Introduction: Hereditary factor X (FX) deficiency (FXD) is a rare autosomal recessive bleeding disorder. Plasma‐derived FX (pdFX) is a high‐purity FX concentrate approved in the United States and Europe for the treatment and prophylaxis of bleeding episodes and for peri‐operative management in patients with hereditary FXD (HFXD). Aim: To review pharmacokinetic dosing, efficacy, and safety data for pdFX as routine prophylaxis for HFXD. Methods: Summary of the published pharmacokinetic and safety data from TEN01, TEN02, TEN05, and real‐world publications of pdFX for prophylaxis. Results: Pharmacokinetic modelling data from the phase 3 TEN01 study supported administration of pdFX 25 IU/kg twice weekly for routine prophylaxis in adolescents/adults (aged ≥12 years). Results from nine paediatric patients in the phase 3 TEN02 study and eight adolescents/adults (aged ≥12 years) in the retrospective data‐collection TEN05 study, along with real‐world evidence, showed that routine prophylaxis with pdFX ≈40 IU/kg twice weekly in patients aged <12 years and pdFX ≈25 IU/kg twice weekly in patients aged ≥12 years was effective in bleeding prevention. Conclusions: pdFX was well tolerated in clinical studies, with no new safety signals identified during routine prophylactic use. Based on current evidence, it is recommended that routine prophylaxis with pdFX be initiated at 25 IU/kg twice weekly in adults/adolescents ≥12 years of age, and at a dosage of 40 IU/kg twice weekly in children <12 years of age. Thereafter, FX levels should be closely monitored, and dosages should be adjusted according to clinical response and to maintain trough levels ≥5 IU/dl.